2021
DOI: 10.3389/fmed.2021.625487
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of Automated Visual Field Report Extraction Platform Using Computer Vision Tools

Abstract: Purpose: To introduce and validate hvf_extraction_script, an open-source software script for the automated extraction and structuring of metadata, value plot data, and percentile plot data from Humphrey visual field (HVF) report images.Methods: Validation was performed on 90 HVF reports over three different report layouts, including a total of 1,530 metadata fields, 15,536 value plot data points, and 10,210 percentile data points, between the computer script and four human extractors, compared against DICOM re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 18 publications
(23 reference statements)
0
7
0
Order By: Relevance
“…This suggests that the structure-function correlations noted in this study may be applicable to a broader group of patients than the previous studies with a more limited scope were able to demonstrate [ 5 7 , 10 15 ]. Furthermore, visual field parameters were extracted using a validated, open-sourced script [ 16 ], illustrating how this script can be applied for future structure-function studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This suggests that the structure-function correlations noted in this study may be applicable to a broader group of patients than the previous studies with a more limited scope were able to demonstrate [ 5 7 , 10 15 ]. Furthermore, visual field parameters were extracted using a validated, open-sourced script [ 16 ], illustrating how this script can be applied for future structure-function studies.…”
Section: Discussionmentioning
confidence: 99%
“…Global indices such as the mean deviation (MD) and pattern standard deviation (PSD) were recorded. For specific sector analyses, pointwise total deviation (TDV), PSD, and mean sensitivity (MS) values were extracted using a validated, open-sourced script ( https://pypi.org/project/hvf-extraction-script/ ) [ 16 ]. The script was used to extract pointwise data from the Ophthalmic Perimetry Values (OPV) DICOM files obtained directly from the Humphrey Visual Field device and PACS system.…”
Section: Methodsmentioning
confidence: 99%
“…24 In this analysis, the raw values of the patient’s retinal sensitivity at each of the HVF 24-2 predetermined points were extracted from pdf scans of the HVFs using a custom data extraction tool based around the Python 25 package ‘hvf extraction script’. 26 This script used Google’s Tesseract Optical Character Recognition 27 to distinguish text inside a digital image and return the relevant text into a useable format. Although the ‘hvf extraction script’ was not originally intended for use on scanned documents, we found that by cleaning the images before processing, we could obtain values for a majority of the retinal sensitivity points.…”
Section: Methodsmentioning
confidence: 99%
“…For specific sector analyses, pointwise total deviation (TD), pattern deviation (PD), TD probability (TDP), and PD probability (PDP) values were extracted using a validated, open-sourced script ( https://pypi.org/project/hvf-extraction-script/ ). 19 The script was used to extract pointwise data from the Ophthalmic Perimetry Values (OPV) DICOM files obtained directly from the Humphrey Visual Field device or extracted JPEG files. The sector wise values were then calculated by averaging the pointwise values across each sector based on prior established sectorial mapping.…”
Section: Methodsmentioning
confidence: 99%